Invariant of Fantastic Robinsonade - E. Y. Kozmina (Научный диалог, 2017)
The article argues that there are two genre versions of the robinsonade - classic one and fantastic one. Fantastic robinsonade not only varies, but transforms the genre structure of the classic robinsonade. The comparison of fiction allows to select “generate model” of this version of robinsonade, that is, an invariant. The article formulates the basic invariant features of fantastic robinsonade. It is shown that it differs from the classic one by the depicting here not the survival of the individual, but the construction of a new human society as the way of survival of mankind. The author emphasizes that the fantastic robinsonade tests on the equivalents of uninhabited islands (e.g., on an alien planet) not only a group of people, but also social ideas. The main compositional and speech form of such a test is philosophical and social conversations. The image of the social structure in a fantastic robinsonade determines the inclusion in a work of dystopian motifs. At the same time a fantastic variant depends on its basis - the classic robinsonade, although often this relationship has a polemical nature.